Intensifying aridity shapes network patterns of soil bacterial communities and geographical distribution of sensitive functional groups in grasslands and farmlands on the Loess Plateau - Jia Wang; Xinyi Guo; Yuru Gao; Kang Zhang; Zhen Yang; Xin Zhao; Jushui Hu; Junyao Deng; Jiaqing Liu; Li Li; Peng Shi; Yanbing Lin; et al. (Applied Soil Ecology, 2026)

Liupao tea alleviates high-fat diet-induced obesity by re-establishing metabolic homeostasis of short-chain fatty acids and chenodeoxycholic acid - Yuru Tan; Xuancheng Wang; Anlong Song; Song Xu; Xueting Lin; Bao Yang; Jichu Luo; Ying Tong; Mingsen Wen; Xuan Guan; Peiting Li; Zhe Luo; et al. (Food Research International, 2026)

Ce, N, S co-doped carbon dots with synergistically enhanced peroxidase-like activity for glucose biosensing and ROS-mediated cytotoxic effect - Xinxin Xu; Junjie Li; Yutong Wu; Jialu Wang; Yuru Lin; Ningning Wang; Zhaohui Li (Analytica Chimica Acta, 2026)

Urban–rural and regional inequalities in PCDD/F exposure across China's urban agglomerations: Insights from a multimedia food-chain model with cooking bioaccessibility - Ying Li; Xianwen Wu; Nazupar Sidikjan; Yuru Chen; Ye Li; Jing Yang; Nan Lin; Huizhong Shen; Min Liu; Ye Huang (Environmental Pollution, 2026)

TomOmics: An integrative multi-omics platform for comparative and functional research in tomato - Yan Wang; Tailai Yang; Yuru Song; Qinqin Yang; Xiao Su; Hongwei Li; Yushan Li; Ming Zhou; Tao Lin (Molecular Plant, 2026)

Inhibition of miR ‐33 Alleviates Inflammation Response in Ctenopharyngodon idella Kidney Cells Induced by Chloroquine/Lipopolysaccharide - Lulu Yang; Mengjun Lin; Weifang Zhao; Yuru Zhang; Xinxin Xu; Xianglin Cao; Ronghua Lu (Journal of Fish Diseases, 2026)
A previous study in our laboratory revealed that microRNA‐33 (miR‐33) regulated autophagy initiation and inflammatory response by targeting Atg5 ; furthermore, in this study, chloroquine (CQ), lipopolysaccharide (LPS) and the miR‐33 inhibitor were transfected into Ctenopharyngodon idella kidney (CIK) cells to explore whether miR‐33 regulated late‐stage autophagy and inflammatory response induced by LPS. The results showed that CQ inhibited the fusion of autophagosome and lysosome and significantly increased the secretion of pro‐inflammatory cytokines ( p p beclin‐1 , atg5 , atg7 and atg12 did not recover after inhibiting miR‐33 ( p > 0.05). But the expression of tnf‐α , il‐6 , il‐1β , il‐8 and nf‐κb , as well as the secretion of TNF‐α, IL‐6, IL‐12 and IL‐1β, were significantly downregulated, and the activities of ALP, SOD and CAT were significantly increased ( p p tnf‐α , il‐6 , il‐1β , il‐8 and nf‐κb ; inhibiting the secretion of TNF‐α, IL‐6, IL‐12 and IL‐1β; and increasing the activities of ACP, ALP, SOD and CAT ( p

Sustainable development assessment of city clusters based on society-water-energy-environment nexus: Degree measurement, spatial differentiation and its factors detection - Haoyuan Liu; Jijun Xu; Dong Wang; Yuru Lin; Xiang Zhang; Jun Xia (Sustainable Cities and Society, 2026)

Study on the durability and microstructure evolution of modified concrete in high altitude cold region - Ziyi Wang; Fujun Niu; Zhanju Lin; Yuru Wang; Xinlong Du; Wenyan Du (Cold Regions Science and Technology, 2026)

Multi-scale investigation of mechanical properties and solidification mechanisms of diverse cementitious materials for solidifying subgrade talik in permafrost regions - Yuru Wang; Fujun Niu; Ziyi Wang; Zhanju Lin; Minghao Liu (Cold Regions Science and Technology, 2025)

Vegetation greening promotes the conversion of blue water to green water by enhancing transpiration - Zhihong Song; Xiaoqi Zhang; Jijun Xu; Yuru Lin; Dunxian She; Yongqiang Wang; Shu Chen; Chen Hu (Journal of Hydrology, 2025)

MiR ‐33‐Mediated Regulation of Autophagy and Inflammation in CIK Cells Through Atg5 - Lulu Yang; Mengjun Lin; Weifang Zhao; Yuru Zhang; Xinxin Xu; Xianglin Cao; Guoxing Nie; Ronghua Lu (Journal of Fish Diseases, 2025)
MicroRNA‐33 (miR‐33) plays a critical role in the regulation of autophagy and inflammatory responses. In this study, C. idella kidney (CIK) cells were transfected with a miR‐33 mimic or inhibitor and Atg5 was overexpressed or silenced to elucidate the regulatory mechanism of miR‐33. Our findings revealed that the miR‐33 mimic significantly decreased the expression of LC3B (a marker of autophagy activation), and the level of autophagy‐related genes ( Beclin‐1 , Atg5 and LC3‐1 ) was also significantly downregulated ( p p Beclin‐1 and Atg5 ( p p Atg5 as a direct target gene of miR‐33. Overexpression of Atg5 significantly upregulated the levels of Beclin‐1 , Atg5 , Atg4C and LC3‐1 , along with a reduction in the secretion of proinflammatory factors (TNF‐α, IL‐12 and IL‐1β). Besides, the activities of superoxide dismutase (SOD) and catalase (CAT) were significantly increased ( p Atg5 expression caused significant downregulation in the expression levels of Beclin‐1 , Atg5 , Atg12 , Atg4C and LC3‐1 , resulting in increased secretion of TNF‐α, IL‐12 and IL‐1β and decreased activity of acid phosphatase (ACP) and SOD ( p Atg5 . This study not only enhances the understanding of the mechanism by which miR‐33 regulates autophagy and inflammation in fish but also provides a theoretical foundation and novel insights to improve disease management in the fish aquaculture industry.

Fatty hepatocyte-derived exosomal miR-122 promotes lipid synthesis and reduces immunocompetence in grass carp (Ctenopharyngodon idella) - Ronghua Lu; Lulu Yang; Wenya Zhang; Shenzong Jia; Mengjun Lin; Jian Sun; Yuru Zhang; Guoxing Nie (Aquaculture, 2023)

Depositional facies and diagenesis of the Lianglitage Formation in northwestern Tazhong Uplift, Tarim Basin, China: implications for the genesis of ultra-deep limestone reservoir - Da Gao; Changsong Lin; Lili Huang; Mingyi Hu; Ping Ren; Chunyan Sun; Yuru Zhao (Arabian Journal of Geosciences, 2021)

Isolation of mitochondria with cubic membrane morphology reveals specific ionic requirements for the preservation of membrane structure - Ketpin Chong; Olivia Li Ling Tan; Zakaria A. Almsherqi; Qingsong Lin; Sepp D. Kohlwein; Yuru Deng (Protoplasma, 2015)

The Processing of Semantic Meaning in Chinese Words and Evoked Brain Topography - Wolfgang Skrandies; Ming-Jang Chiu; Yuru Lin (Brain Topography, 2004)